Internal Jugular Vein Fenestration and Duplication: Anatomical Findings, Prevalence, and Literature Review - Wang, Xiqian; Peng, Liwei; Guo, Haixing; Hernesniemi, Juha; Xiong, Xuepeng; Andrade-Barazarte, Hugo; Qian, Rongjun (Frontiers in Surgery, 2020)
Background: Comprehensive knowledge of the internal jugular vein (IJV) regarding its anatomical variations and the pattern of its course is valuable for preventing unexpected injuries during surgical procedures or central venous access. IJV anatomical anomalies such as fenestration and duplication are rare, mainly represented by case reports and intraoperative findings. Objective: To present two additional cases of IJV anomalies and highlight its clinical presentation, anatomical characteristics, management and prevalence through an extensive literature review. Methods and case reports: From January 2017 to December 2018, we retrospectively collected data of 221 patients undergoing neck dissection (ND) procedures and identified two patients with IJV anomalies (fenestration and duplication) providing a clinical prevalence of approximately 0.9%. The IJV fenestration referred to an IJV bifurcation that reunites proximal to the subclavian vein, whereas in the IJV duplication both branches remain separated. In both of our cases, the spinal accessory nerve crossed the window between the IJV branches. Conclusion: Anatomical variations are more likely to be identified intraoperatively or incidentally, and due to the risk of SAN and vascular injury, special attention should be taken to identify them preoperatively in order to reduce the risk of iatrogenic injury and unexpected complications.